Analysis of Indonesian Palm Oil Competitiveness in the Main Export Destination Countries - Maulana, Fahrul Rozi; Sukiyono, Ketut; Nusril; Sriyoto (Indonesian Journal of Agricultural Research, 2023)
Indonesia is the largest palm oil producing country in the world with a production volume of nearly 43 million tons/year. The high production of Indonesian palm oil is a new opportunity that needs to be developed in this globalization era to compete with its main competitors. Therefore, an analysis is needed in order to discover the competitiveness of Indonesian palm oil commodity in the main export destination countries. Export is an activity conducted by a country by selling its products abroad using the payment system, quality, quantity, and other sales terms that have been agreed upon by the exporting and importing countries. This study aims to analyze the level of competitiveness of Indonesian palm oil exports in the Asian and European markets represented by six countries: India, Malaysia, Singapore, the Netherlands, Italy, and Spain. The analytical method used is Revealed Competitive Advantage (RCA) to see the comparative advantage and to determine whether the performance of Indonesian palm oil products in the main export destination countries increases or decreases by using the Revealed Comparative Advantage Index (RCA Index) calculation. The data used are secondary data in the form of time series during the period of 2014 to 2020 and cross sections of the main export destination countries of Indonesian palm oil. The results of the calculation of the RCA value show that in the period 2014 to 2020 the RCA value of Indonesian palm oil products in the main export destination countries is higher than one (> 1). Thus, Indonesian palm oil products have a comparative advantage in the main exports of destination countries from year to year. In contrast to the RCA index calculation results in this study, Indonesian palm oil products are still able to show a positive trend every year. This is proven by certain years’ RCA index of the main export destination countries: India, Malaysia, Singapore, the Netherlands, Italy, and Spain is still less than one (<1) even though the average RCA index value for each country is higher than one (>1). Hence, it can be said that the performance of Indonesian palm oil products increases or decreases frequently every year in each of the main export destination countries.